2022
DOI: 10.33084/bjop.v5i4.3801
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Molecular Docking and ADMET Analysis for Drug Development of Phytoestrogens Compound with Its Evaluation of Neurodegenerative Diseases

Abstract: Neurodegenerative disease is one of the problems faced by postmenopausal women due to estrogen deficiency. Phytoestrogen compounds can be used as an alternative treatment for diseases caused by estrogen deficiency by binding to their receptors through the estrogen receptor (ER) dependent pathway. With in silico studies, this study aims to predict how phytoestrogen compounds will stop neurons from dying by using the dependent ER pathway. Genistein, daidzein, glycitein, formononetin, biochanin A, equol, pinoresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The binding affinity and inhibition potential of the inhibitors were tested by performing molecular docking studies on the autodock vina window on PyRx interface. Discovery Studio 2021 Client [20] was used in post docking analysis. The top hits' structural representations in relation to the binding affinities were also examined.…”
Section: Molecular Docking and Post Docking Analysismentioning
confidence: 99%
“…The binding affinity and inhibition potential of the inhibitors were tested by performing molecular docking studies on the autodock vina window on PyRx interface. Discovery Studio 2021 Client [20] was used in post docking analysis. The top hits' structural representations in relation to the binding affinities were also examined.…”
Section: Molecular Docking and Post Docking Analysismentioning
confidence: 99%
“…Firstly, the protein was converted to "pdbqt" format and a grid box was set to cover the active site of the crystal structure with the following dimensions in Å: center (X, Y, Z) = (13.42, 7.19, 35.65); dimensions (X, Y, Z) = (5.72, 6.39, 14.01) with an exhaustiveness of 8. The Discovery Studio 2021 Client was used in post-docking analysis [39]. An extensive qualitative structural assessment and examination of the structural representations of the three best hits were carried out to examine the scaffolds and functional groups responsible for the binding interactions observed in the post-screening analysis.…”
Section: Virtual Screening and Post-screening Analysesmentioning
confidence: 99%
“…Hence, a predictive ADMET study was conducted using the OSIRIS Property Explorer tool [41] to estimate the toxicity profile and druglikeness of the best 10 hits to propose whether they can pass as being orally active drugs [42]. The following pharmacokinetic properties were examined: molecular weight and solubility (log S), which are determinants of the degree to which a compound can penetrate the biological membrane [39]; hydrophilicity (log P) to estimate the dissolution of compounds in a liquid membrane; topological polar surface area (TPSA) associated with membrane permeability [43]; and drug score, a single value from the combination of all the properties listed above [44] and toxicity risk combining irritant, tumorigenic, mutagenic, and reproductive risks [45]. Druglikeness, a value that determines the consistency in properties of a compound as a drug candidate, was also examined [46].…”
Section: In Silico Druglikeness Predictionmentioning
confidence: 99%
“…The results showed that the equol compound was similar to 17‐β‐estradiol, which is a native ligand. The same compound was shown to bind to the ERα (1A52) and ERβ (5TOA) receptors, which further helped to inhibit neurodegeneration through an ER‐dependent pathway (Muslikh et al, 2022).…”
Section: Phytoestrogens and Their Therapeutic Effectsmentioning
confidence: 99%